MECHANISMS OF MANAGEMENT OF ENTREPRENEURIAL ACTIVITY IN CONDITIONS OF UNCERTAINTY IN THE REGIONS OF UKRAINE - Zahorskyi, Volodymyr; Kysil, Bohdan (Public Management and Policy, 2026)
The study emphasizes that measures based on the principle of stimulation should form the basis for the formation of mechanisms to support entrepreneurship in conditions of uncertainty. It has been determined that the effectiveness of the implementation of mechanisms to stimulate entrepreneurship should consist not only in the direct development of entrepreneurship, but also take into account the reverse economic and social effect for the state as a public authority. It has been proven that the effective implementation of methods for managing entrepreneurial activity in conditions of uncertainty on the part of public administration is achieved through a combination of administrative and managerial functions, mutual understanding of business needs on the part of public authorities, and, accordingly, social and economic state needs on the part of entrepreneurial structures. The study identifies and systematizes the main mechanisms of public administration aimed at developing entrepreneurship and assesses the effectiveness of their use, as well as identifies the factors that currently need to be addressed to increase the stability of business structures in conjunction with reforming approaches to public management of entrepreneurship in conditions of uncertainty for further sustainable economic development. It has been proven that the relevance of the issue of developing and implementing effective mechanisms for managing entrepreneurial activity in the economic and political conditions in which Ukraine finds itself lies in the interaction and establishment of partnerships between business and public authorities, and in the joint search for optimal mechanisms to stimulate entrepreneurship for the establishment of a stable economy in conditions of uncertainty. The establishment of effective and stimulating public management in crises forms the basis for the functioning of business management mechanisms to ensure further sustainable economic development. The existing local factors of uncertainty inherent in entrepreneurship have grown into more global and unpredictable ones and have become one of the drivers for the search for new and the development of existing incentive mechanisms by state and local authorities to ensure the proper functioning and stimulation of the economy of the country and regions.